Pericardial mesothelioma mimicking mediastinal lymphoma and systemic rheumatic disease: a case report - Hirnle, Grzegorz; Kapałka, Michał; Krawiec, Michał; Hrapkowicz, Tomasz (Frontiers in Oncology, 2025)
IntroductionPericardial mesothelioma is an exceedingly rare pericardial neoplasm. It has atypical clinical symptoms and imaging characteristics that often lead to an inconclusive diagnosis. The diagnosis of a rare tumor such as pericardial mesothelioma, which can present with a variety of manifestations, requires a multidisciplinary approach.Case presentationA 36-year-old Caucasian female patient without significant past medical history was admitted to the hospital with chest pain and a high fever and was diagnosed with acute pericarditis. The following month, the patient was treated for sepsis; during this hospitalization, lab tests for antinuclear antibodies (ANA) turned out to be positive. Concurrently, mediastinal lymphadenopathy was observed. Given the suspicion of mediastinal lymphoma, a mediastinoscopy with lymph node biopsy was performed. Following a negative biopsy result, positron emission tomography combined with computed tomography (PET/CT) and blood immunophenotyping were performed. Both tests ruled out a diagnosis of lymphoma. Concurrently, the patient was hospitalized in the rheumatology department due to positive ANA results. There, in addition to the ANA titer at a level of 1:320, lupus anticoagulant was detected. The patient was diagnosed with systemic lupus erythematosus (SLE) and initiated on chronic steroid therapy. As heart failure progressed, the patient was admitted to the cardiology department. Tissue Doppler echocardiography and cardiac magnetic resonance imaging (MRI) revealed features indicative of constrictive pericarditis. The patient underwent a pericardiectomy with satisfactory results. However, the pathology result of the pericardium remained equivocal. The patient was readmitted 3 months later with severe circulatory failure, and a salvage procedure of pericardiectomy was performed. Histopathological examination of the sections confirmed the diagnosis of pericardial epithelioid mesothelioma. The patient died after 3 weeks of palliative care.ConclusionsIn the differential diagnosis of relapsing and resultant constrictive pericarditis, neoplastic processes that may mimic systemic rheumatic diseases should also be considered. Pericardial mesothelioma is a very rare diagnosis and may result in increased ANA titers, particularly anti-dense fine speckled 70 (DFS70) antibodies.